Improving Scientific Argumentation Through The Hierarchy Of Inquiry - Probosari, Riezky Maya; Ramli, Murni; *, Sajidan (Sebelas Maret University, 2016)
This study examined how studentsâ scientific argumentation changed over as they participated in hierarchy of inquiry learning. The hierarchy of inquiryÂ is a comprehensive approach in which studentsÂ working for an extended period of time that integrated several ways of inquiry systematically to investigate and respond to a complex question, problem, or challenge. ThisÂ action research wasÂ conducted in Biology Teacher Education Program Faculty of Teacher Training and Education Sebelas Maret University.Â The students, who were at the 4rd semester and who studied the class of Plant Embryology, were purposely selected.Â Â The data were collected from interviews with the researchers, classroom observations, and collection of student portfolios. The scientific argumentationÂ Â was measured using modified Toulminâs Argument Pattern (TAP) with four kinds of argument elements:Â claim,Â evidence, reasoning, and rebuttal which presented in oral and written.Â The results showed that students who experienced with the hierarchy of inquiry performed better scientific argumentationÂ Â which reflecting their higher-order thinking abilities.Â Â Â Â Â We conclude that hierarchy of inquiryÂ Â is possible in fostering studentâs scientific argumentation,Â Â Â doing some inquiry activities, and thus make a positive impact onÂ Â scientific argumentation ability .Â The findings can be helpful in the process of designing the new curricula for teacher candidates in order to foster scientific inquiry.